Menelisik Dinamika Radikalisme Gen Z Perempuan di Facebook - Eko Saputra (Islamica: Jurnal Studi Keislaman, 2019)
Nowadays, the proliferation of radicalization among the so-called Generation Z in the online space shows an alarming phenomenon. This article is to explore how online media is used by a woman of generation Z, Nurdhania, to access ideological propaganda of the Islamic State in Iraq and Syria (ISIS). The questions are how was the propaganda embedded in Nurdhania’s mind? How big are the Nurdhania’s commitment, involvement, and struggle in supporting ISIS? To answer these questions, this research used the method of ethnography, through the internet, of blogs and social media that belong to Nurdhania, and conducted an interview with one of her relatives in Yogyakarta. This article argues that Nurdhania was exposed to the ideology of ISIS because of (1) her confusion with the uncertainty of the future; (2) a ‘moral panic’ she had experienced; and (3) the Islamic State highlighted as the most ideal state system.